Quantification of Agnuside in Human Plasma with a Novel High-Performance Liquid Chromatographic Method and Pharmacokinetic Study - EGELİ D.; TIRIS G.; Tekkeli E. K. (My University, 2025)
This study presents a combination of High Performance Liquid Chromatography (HPLC) and ultraviolet (UV) detection that provides the quantification of agnuside in human plasma specimens. Reverse-phase chromatographic separation was carried out with C18 column (150 mm x 4.6 mm x 5 mu m), at 25 degrees C with isocratic elution of the mobile phase containing methanol: 0.1% formic acid (35:65 v/v) at 0.6 mL/min flow rate. Experiments were carried out at a wavelength of 258 nm. The retention time of the analyte is 9.70 +/- 0.01 min. The developed technique was validated based on the International Conference on Harmonization guideline. The correlation coefficient of the technique was 0.9915, and the calibration range was 5-125 mu g/mL. The recovery value of the proposed method was found to be 101.4%, and the precision of the method was calculated as 6.35 with the highest RSD% value. A pharmacokinetic study was performed by administering agnuside to a healthy volunteer.
Keywords: Tıp; Yaşam Bilimleri; Biyokimya; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Analitik Kimya; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Life Sciences; Biochemistry; Molecular Biology and Genetics; Cytogenetic; Chemistry; Analytical Chemistry; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Biyokimyasal Araştırma Yöntemleri; Biyoloji Ve Biyokimya; Yaşam Bilimleri (Life); Kimya Analitik; Temel Bilimler (Sci); Biyokimya Ve Moleküler Biyoloji; Moleküler Biyoloji Ve Genetik; Biochemical Research Methods; Biology & Biochemistry; Life Sciences (Life); Chemistry Analytical; Natural Sciences (Sci); Biochemistry & Molecular Biology; Molecular Biology & Genetics; İlaç Keşfi; Biyokimya (tıbbi); Kimya (çeşitli); Genel Kimya; Filtrasyon ve Ayırma; Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Fizik Bilimleri; Drug Discovery; Biochemistry (medical); Chemistry (miscellaneous); General Chemistry; Filtration and Separation; Structural Biology; Molecular Biology; Clinical Biochemistry; Cancer Research; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology; Physical Sciences